Cognitive spirit of kindergarten students (Journal of the College of Basic Education, 2024)
The current research aims to identify the cognitive spirit among the students of the Kindergarten Department. The research relied on the descriptive approach. The research sample was (200) female students from the Kindergarten Department in the College of Basic Education / Al-Mustansiriya University. Based on the theories and previous studies related to the subject of their research, as the cognitive spirit scale in its final form included (38) items, and the two researchers verified the psychometric characteristics of the tool, and the following results were reached:- The students of the Kindergarten Department have a spirit of knowledge, as the results came with an arithmetic mean higher than the hypothetical mean of the scale.